Visualization of a hyaluronan network on the surface of silicone-hydrogel materials - Wygladacz KA (Dove Medical Press, 2016)
Katarzyna A Wygladacz, Daniel J Hook Vision Care, Bausch & Lomb Incorporated, Rochester, NY, USA Abstract: Biotrue multipurpose solution (MPS) is a bioinspired disinfecting and conditioning solution that includes hyaluronic acid (HA) as a natural wetting agent. Previous studies demonstrated that HA sorbed from Biotrue MPS on both conventional and silicone hydrogel (SiHy) contact lens materials; an in vitro simulated-wear test validated the presence of HA on the lens surfaces for as long as 20 hours. In this study, the morphology and distribution of HA sorbed from both Biotrue and pure HA solution on SiHy contact lens surfaces was examined. Atomic force microscopy imaging was used to illustrate the topography of fresh SiHy contact lens materials before and after incubation with 0.1% (w/v) HA solution. The distribution, as well as fine details of the HA network, were resolved by first staining HA with Gram’s safranin, then imaging with confocal laser-scanning microscopy and differential interference-contrast microscopy. In this approach, SiHy materials take up the dye (safranin) nonspecifically, such that the resultant safranin–HA complex appears dim against the fluorescent lens background. Balafilcon A was chosen as the representative of glassy SiHy lenses that require postpolymerization plasma treatment to increase wettability. Senofilcon A and samfilcon A were chosen as representatives of SiHy materials fabricated with an internal wetting agent. A confluent and dim HA–safranin network was observed adhered to balafilcon A, senofilcon A, and samfilcon A lens surfaces incubated with either 0.1% (w/v) HA solution or Biotrue MPS. Therefore, the conditioning function provided by Biotrue MPS may be in part explained by the presence of the HA humectant layer that readily sorbs on the various types of SiHy contact lens materials. Keywords: contact lens, hyaluronan, MPS, AFM, CLSM, DIC microscopy